Tungsten carbide cobalt-based hard alloy and preparation method thereof
By adopting special component design and low pressure + fast-cooling sintering process in the preparation of nanocrystalline WC-Co-based cemented carbide, the problems of low strength, poor toughness and high cost of nanocrystalline WC-Co-based cemented carbide are solved, and the problem of low strength, poor toughness and high cost are achieved. High strength, high toughness and low cost nanocrystalline carbide preparation.
Patent Information
- Application Number
- CN202311005809.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-18
AI Technical Summary
The existing nanocrystalline WC-Co-based cemented carbide products have low strength, poor toughness, high cost, and uneven dispersion of inhibitors leads to a decrease in strength.
The nanocrystalline WC-Co-based cemented carbide is prepared by using a special component design combined with low pressure + fast-cool sintering. By controlling the sintering process and adding ultrafine W powder, the growth of WC is inhibited and the face-centered cubic structure of the bonded phase Co is maintained. , improve the strength and toughness of the alloy.
The prepared nanocrystalline WC-Co-based cemented carbide has high strength, high toughness, improved service life, low cost, and is market-competitive.
Smart Images

Figure CN119464875A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of cemented carbide materials and relates to a nanocrystalline WC-Co based cemented carbide with high strength and high toughness and a preparation method thereof. Background Art
[0002] WC-Co cemented carbide is made into various tools due to its high strength and hardness and is widely used in mechanical processing, mining, road milling, mold processing and other fields. With the acceleration of industrialization in countries around the world, the vigorous development of the electronic information industry and the enhancement of people's environmental awareness, various important new materials and key products are constantly emerging, and the preparation technology of cemented carbide products is gradually developing towards near-nano or even nanocrystalline sizes. At present, the preparation technology of nanocrystalline cemented carbide mainly focuses on the following aspects: ① Reducing the Co content to reduce the WC liquid phase sintering effect, such as binderless nanocrystalline cemented carbide, but this type of cemented carbide product has low strength and narrow practicality and application field; ② Selecting nano-scale WC to prepare nanocrystalline cemented carbide, but this method has a high cost of developed cemented carbide products due to the high cost of nano WC; ③ Adding a large amount of chromium carbide and vanadium carbide as the main grain inhibitor to prepare nanocrystalline cemented carbide, but in this method, the inhibitors such as chromium carbide and vanadium carbide are difficult to disperse evenly due to excessive amounts, and the strength and toughness of the prepared nanocrystalline cemented carbide products are limited. Once component segregation occurs, the strength will be reduced. In view of the above problems, the present invention proposes a preparation method of a nanocrystalline WC-Co-based cemented carbide with high strength and high toughness. Summary of the invention
[0003] In view of the above-mentioned shortcomings existing in the prior art, in order to overcome the problems of low strength, poor toughness, high cost, etc. of nanocrystalline WC-Co based cemented carbide products, the present invention provides a WC-Co based cemented carbide with high wear resistance and a preparation method thereof. The successful preparation of the alloy can reduce the replacement frequency of WC-Co based alloy wear-resistant tools / parts, thereby reducing production costs and achieving high-quality and efficient production.
[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0005] In order to achieve the above purpose, the present invention adopts the following technical scheme: a nanocrystalline WC-Co based cemented carbide material with high strength and high toughness, which is prepared by special component design combined with low pressure + rapid cooling sintering. First, WC (carbon content 6.10%-6.15%, particle size 0.5μm-0.6μm), ultrafine W powder, ultrafine Co powder, Cr 3 C 2, VC are used as raw materials, and the mixture is dried and granulated at 75°C after mixed ball milling for 40 hours, and then pressed at 5MPa to obtain a green billet sample. Finally, a nanocrystalline WC-Co based alloy with high strength and high toughness is obtained through a specific low-pressure sintering + rapid cooling process.
[0006] The tungsten carbide cobalt-based hard alloy of the present invention comprises the following raw materials in parts by weight: 8-10 parts of cobalt powder, 0-1.5 parts of tungsten powder, 0.35-0.45 parts of chromium carbide, 0.25-0.35 parts of vanadium carbide, and the balance is tungsten carbide powder.
[0007] The above-mentioned tungsten carbide cobalt-based hard alloy preferably contains the following raw materials in parts by weight: 9 parts of cobalt powder, 0.5-1.5 parts of tungsten powder, 0.4 parts of chromium carbide, 0.3 parts of vanadium carbide, and the balance is tungsten carbide powder.
[0008] The preparation method of the above-mentioned tungsten carbide cobalt-based cemented carbide comprises the following steps:
[0009] S1: weigh raw materials tungsten carbide powder, ultrafine tungsten powder, ultrafine cobalt powder, chromium carbide, and vanadium carbide according to proportion, and obtain a mixed material after ball milling;
[0010] S1: Pressing molding;
[0011] S3: Sintering; The sintering process includes the following stages in sequence:
[0012] Dewaxing: heat to 450-550℃, keep warm for 0.5h;
[0013] Vacuum sintering: heat to 1350℃ and keep warm for 1h;
[0014] Low-pressure sintering: heat to 1380°C, furnace pressure 0.9MPa, keep warm for 1.5h;
[0015] S4: After sintering is completed, the furnace is cooled.
[0016] As we all know, the grain growth of WC cemented carbide adopts the liquid phase sintering method, that is, WC is continuously dissolved and precipitated in the binding phase Co, so that the WC grains can grow. Therefore, in order to obtain nanocrystalline cemented carbide, in addition to using finer WC raw materials, the only way is to try to inhibit the growth of WC in the liquid phase sintering process, that is, the existing technology usually uses a large amount of Cr 3 C 2 , VC and other inhibitors or reduce the Co content, that is, the liquid phase content during the sintering process, but the problem caused by uneven dispersion is reduced strength. The present invention uses a small amount of Cr 3 C 2 , VC inhibitor, to avoid excessive dispersion resulting in uneven dispersion and reduced strength, but Cr 3 C 2The reduction of the amount of VC inhibitor will also reduce the inhibitory effect. Therefore, in addition to using inhibitors, how to hinder the melting and precipitation of WC during sintering is the innovation of the present invention.
[0017] The melting-precipitation process of WC in the Co phase is like a reversible reaction. Since W has a certain solubility in the Co phase, the solubility will increase with the increase of sintering temperature. Therefore, the present invention controls the sintering process and actively adds ultrafine W powder to the Co phase to reduce the solubility of the bonding phase Co to W in WC during liquid phase sintering, thereby inhibiting the growth of WC to prepare nanocrystalline cemented carbide. In addition, the bonding phase Co usually presents a close-packed hexagonal structure at room temperature. Since the face-centered cubic structure has 12 slip planes, its strength and toughness are better; the close-packed hexagonal structure has only 3 slip planes, and its strength and toughness are poor. These two Co phase structures mainly rely on dislocation expansion to complete the crystal transformation. When cooling after high-temperature sintering, the stable face-centered cubic Co at high temperature will gradually transform to a close-packed hexagonal crystal as the temperature decreases. However, due to the addition of ultrafine W powder, W atoms will be concentrated on the dislocation of the Co phase, increasing the dislocation energy of the crystal, hindering the wide decomposition of dislocations, thereby reducing the width of stacking faults, that is, reducing the potential formation of Co germs of the close-packed hexagonal crystal. At the same time, because the W powder is evenly distributed in the Co phase and has a "pinning" effect, the germ is not easy to move, which also increases the transformation temperature of the crystal.
[0018] A further improvement is that in the above preparation method, after sintering is completed, forced air cooling is used for cooling, and the cooling rate is about 10-15°C / min.
[0019] Combined with the rapid cooling process of the present invention, the face-centered cubic structure of the bonding phase Co existing at high temperature can be better retained at room temperature. The nanocrystalline WC-Co based cemented carbide prepared by the method exhibits high strength and high toughness.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The beneficial effects of the present invention are as follows: (1) the preparation method of the alloy is simple, easy to control, and has no additional steps; (2) the nanocrystalline cemented carbide prepared by the method has high strength and high toughness, and the service life of the prepared tools / parts is significantly improved; (3) the high-strength and high-toughness nanocrystalline cemented carbide prepared by the method can reduce the replacement frequency of tools / parts, thereby improving work efficiency. At the same time, compared with the production method of nanocrystalline cemented carbide using finer nano WC as raw material, the cost is lower and it is more competitive in the market. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the high-strength, high-toughness nanocrystalline cemented carbide of the present invention; DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to better understand the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0024] In the following examples, the raw materials include ultrafine tungsten carbide (carbon content range 6.10%-6.15%; average particle size range 0.5μm-0.6μm), ultrafine tungsten powder (average particle size less than or equal to 0.4μm), and ultrafine cobalt powder (average particle size less than or equal to 1μm).
[0025] Example 1
[0026] A method for preparing nanocrystalline WC-Co based cemented carbide is as follows:
[0027] 1. Raw material ratio: weigh the raw materials according to the weight parts in Table 1.
[0028] 2. Ball milling: Add the raw materials, 2%wt paraffin wax and 0.04% stearic acid into the ball mill. The grinding body is alloy balls (diameter 10mm), the ball-to-material ratio is 10:1; the grinding medium is hexane, and the amount of hexane added is 600mL / kg; the ball milling is carried out in a drum-type ball mill at a speed of 72r / min for 40h. After the ball milling is completed, the slurry is screened and sieved at 75℃.
[0029] The dry material is obtained by vacuum drying, and then granulated to obtain a mixed material;
[0030] 3. Pressing: Obtain green blank sample with a pressing pressure of 5 MPa.
[0031] 4. Sintering: The green billet is sintered in a low-pressure sintering furnace. The specific process is divided into four stages:
[0032] The first stage of dewaxing was to increase the temperature from room temperature to 250°C at a rate of 4°C / min, then to 320°C at a rate of 1.2°C / min, then to 370°C at a rate of 0.3°C / min and keep it for 3h, then to 450°C at a rate of 2.6°C / min and keep it for 30min, and then to 550°C at a rate of 3.3°C / min and keep it for 30min to complete the dewaxing;
[0033] The second stage is vacuum sintering, i.e. firstly, the temperature is raised to 650°C at 3.3°C / min, then raised to 1100°C at 4.5°C / min and kept at that temperature for 1 hour. After the heat preservation is completed, argon gas is introduced to adjust the vacuum degree in the furnace (the vacuum degree is 3 kPa), and then the temperature is further raised to 1350°C at 4°C / min and kept at that temperature for 1 hour to complete the vacuum sintering;
[0034] The third stage is low-pressure sintering. The temperature is raised to 1380°C at a rate of 1°C / min, then the vacuum is turned off and the pressure in the furnace is filled with argon to reach 0.9 MPa. Then the sintering is continued at this temperature for 90 minutes.
[0035] The fourth stage is cooling, which is performed by cooling down to room temperature (cooling rate is about 2°C / min) to obtain a WC-Co based cemented carbide.
[0036] 5. The prepared WC-Co based cemented carbide is subjected to surface polishing treatment.
[0037] The surface morphology and physical properties of the prepared alloy were characterized. The metallographic structure of the prepared alloy sample is A02B00C00, and the average grain size of WC, coercive force, Rockwell hardness, Vickers hardness HV30, bending strength, and fracture toughness are respectively 440nm, 28.2kA / m, 92.9HRA, 1910, 3919MPa, and 9.2MPa·m 1 / 2 .
[0038] Example 2
[0039] A method for preparing nanocrystalline WC-Co based cemented carbide, wherein the steps are the same as those in Example 1.
[0040] Similarly, by characterizing the surface morphology and physical properties, the metallographic structure of the prepared alloy sample is A02B00C00, and the average grain size, coercive force, Rockwell hardness, Vickers hardness HV30, flexural strength, and fracture toughness of WC are 330nm, 35.2kA / m, 93.6HRA, 1970, 4416MPa, and 9.5MPa·m, respectively. 1 / 2 .
[0041] Example 3
[0042] A method for preparing nanocrystalline WC-Co based cemented carbide, wherein the steps are the same as those in Example 1.
[0043] Similarly, by characterizing the surface morphology and physical properties, the metallographic structure of the prepared alloy sample is A02B00C00, and the average grain size, coercive force, Rockwell hardness, Vickers hardness HV30, flexural strength, and fracture toughness of WC are respectively 260nm, 40.4kA / m, 94.2HRA, 2020, 4896MPa, and 10.1MPa·m. 1 / 2 .
[0044] Example 4
[0045] The same as in Example 1. The difference is that ultrafine W powder is added, namely 1.5%wt ultrafine W powder (average particle size 0.4μm) and 89.50%wt ultrafine WC (carbon content range 6.10%-6.15%; average particle size range 0.5μm-0.6μm), and the rest is the same as in Example 1.
[0046] Similarly, by characterizing the surface morphology and physical properties, the metallographic structure of the prepared alloy sample is A02B00C00, and the average grain size, coercive force, Rockwell hardness, Vickers hardness HV30, flexural strength, and fracture toughness of WC are respectively 230nm, 41.9kA / m, 94.3HRA, 2030, 3822MPa, and 9.2MPa·m 1 / 2 .
[0047] Example 5
[0048] A method for preparing nanocrystalline WC-Co based cemented carbide, wherein the raw material ratio is the same as that of Example 3. Except for the following steps, the remaining steps are the same as those of Example 3.
[0049] 4. Sintering
[0050] The fourth stage of cooling: forced air cooling is used for cooling, and the cooling rate is about 10°C / min to obtain WC-Co based cemented carbide.
[0051] Similarly, by characterizing the surface morphology and physical properties, the metallographic structure of the prepared alloy sample is A02B00C00, and the average grain size, coercive force, Rockwell hardness, Vickers hardness HV30, flexural strength, and fracture toughness of WC are respectively 210nm, 41.5kA / m, 94.3HRA, 2030, 5326MPa, and 11.1MPa·m. 1 / 2 .
[0052] Example 6
[0053] A method for preparing nanocrystalline WC-Co based cemented carbide, wherein the raw material ratio is the same as that of Example 3. Except for the following steps, the remaining steps are the same as those of Example 3.
[0054] 4. Sintering
[0055] The fourth stage of cooling: forced air cooling is used for cooling at a cooling rate of about 15°C / min to obtain WC-Co based cemented carbide. The SEM image of the prepared alloy is shown in the figure below: Figure 1 .
[0056] Similarly, by characterizing the surface morphology and physical properties, it was found that the metallographic structure of the alloy sample prepared by this method was A02B00C00, and the average grain size, coercive force, Rockwell hardness, Vickers hardness HV30, flexural strength, and fracture toughness of WC were 190nm, 42.3kA / m, 94.3HRA, 2060 HV30, 5860MPa, and 11.3MPa·m, respectively. 1 / 2 .
[0057] Example Ultrafine tungsten carbide Ultrafine tungsten powder Ultrafine cobalt powder Chromium Carbide Vanadium Carbide Example 1 90.3 0 9 0.4 0.3 Example 2 89.8 0.5 9 0.4 0.3 Example 3 89.3 1 9 0.4 0.3 Example 4 88.8 1.5 9 0.4 0.3 Example 5 89.3 1 9 0.4 0.3 Example 6 89.3 1 9 0.4 0.3
[0058] Table 1
[0059] The above is the best embodiment of the present invention, but the following contents are the protection points of the present invention:
[0060] (1) Composition: WC-Co based alloy with W content of 0%-1.5%, chromium carbide content of 0.35%-0.45%, and vanadium carbide content of 0.25%-0.35%;
[0061] (2) Sintering process: The low pressure + rapid cooling process ensures that the prepared nanocrystalline cemented carbide binder phase Co presents a face-centered cubic structure;
[0062] (3) Application areas: This technology can be used in all WC-xCo (x = 8% -10%) alloys to improve their strength and toughness.
[0063] The common sense such as the known specific structures and characteristics in the scheme of the present invention is not described in detail here. The ordinary technicians in the relevant field are aware of all the common technical knowledge in the technical field of the invention before the application date or priority date, can obtain all the existing technologies in the field, and have the ability to apply the conventional experimental means before that date. The ordinary technicians in the relevant field can improve and implement this scheme in combination with their own abilities under the enlightenment given by this application. Some typical known structures or known methods should not become obstacles for the ordinary technicians in the relevant field to implement this application. It should be pointed out that for the technicians in this field, without departing from the structure of the present invention, several deformations and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. A tungsten carbide cobalt-based hard alloy, characterized in that: The invention comprises the following raw materials in parts by weight: 8-10 parts of cobalt powder, 0.5-1.5 parts of tungsten powder, 0.35-0.45 parts of chromium carbide, 0.25-0.35 parts of vanadium carbide, and the balance is tungsten carbide powder.
2. The tungsten carbide cobalt-based hard alloy according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 9 parts of cobalt powder, 1 part of tungsten powder, 0.4 parts of chromium carbide, 0.3 parts of vanadium carbide, and the balance is tungsten carbide powder.
3. The tungsten carbide cobalt-based cemented carbide according to claim 1, characterized in that: The tungsten powder is ultrafine W powder.
4. The tungsten carbide cobalt-based cemented carbide according to claim 1, characterized in that: The carbon content of the tungsten carbide powder is 6.10%-6.15%, and the particle size is 0.5μm-0.6μm.
5. The tungsten carbide cobalt-based cemented carbide according to claim 2, characterized in that: The cobalt powder is ultrafine cobalt powder.
6. A method for preparing tungsten carbide cobalt-based hard alloy, characterized in that: The steps include: S1: weigh the raw materials tungsten carbide powder, ultrafine tungsten powder, ultrafine cobalt powder, chromium carbide and vanadium carbide according to proportion; S2: ball milling; S3: Pressing and forming; S4: Sintering; the sintering process includes the following stages in sequence: Dewaxing: heat to 450-550℃, keep warm for 0.5h; Vacuum sintering: heat to 1350℃ and keep warm for 1h; Low-pressure sintering: heat to 1380°C, furnace pressure 0.9MPa, keep warm for 1.5h; S5: After sintering is completed, the furnace is cooled.
7. The preparation method according to claim 6, characterized in that: Described step 5 adopts the following method: S5: After sintering, forced air cooling is used for cooling at a cooling rate of 10°C / min.
8. The preparation method according to claim 6, characterized in that: Described step 5 adopts the following method: S5: After sintering, forced air cooling is used for cooling at a cooling rate of 15°C / min.
9. The preparation method according to claim 6, characterized in that: Described step 4 adopts the following method: S4: Sintering; Sintering includes the following stages in sequence: Dewaxing: The sintering temperature is room temperature-550℃, that is, firstly increase the temperature from room temperature to 250℃ at a rate of 4℃ / min, then increase it to 320℃ at 1.2℃ / min, then increase it to 370℃ at 0.3℃ / min and keep it for 3h, then increase it to 450℃ at 2.6℃ / min and keep it for 30min, then increase it to 550℃ at 3.3℃ / min and keep it for 30min to complete the dewaxing; Vacuum sintering: The sintering temperature is 550-1350℃, that is, first increase the temperature to 650℃ at 3.3℃ / min, then increase the temperature to 1100℃ at 4.5℃ / min and keep it for 1h. After the insulation is completed, argon gas is introduced to adjust the vacuum degree in the furnace (the vacuum degree is 3kPa), and then continue to increase the temperature to 1350℃ at 4℃ / min and keep it for 1h to complete the vacuum sintering; Low-pressure sintering: The sintering temperature is 1350-1410°C, that is, the temperature is continuously raised at 1°C / min to 1380°C, and then the vacuum is turned off, argon is charged to make the pressure in the furnace reach 0.9MPa, and then the sintering is continued at a temperature of 90 minutes.